If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 25x + 7Y + -7 = 0 Reorder the terms: -7 + 7Y + 25x = 0 Solving -7 + 7Y + 25x = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7Y + 7 + 25x = 0 + 7 Reorder the terms: -7 + 7 + 7Y + 25x = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 7Y + 25x = 0 + 7 7Y + 25x = 0 + 7 Combine like terms: 0 + 7 = 7 7Y + 25x = 7 Add '-25x' to each side of the equation. 7Y + 25x + -25x = 7 + -25x Combine like terms: 25x + -25x = 0 7Y + 0 = 7 + -25x 7Y = 7 + -25x Divide each side by '7'. Y = 1 + -3.571428571x Simplifying Y = 1 + -3.571428571x
| 7x-9=2x+5 | | -4=-x+3 | | p=3+2p | | x/15-7=-2 | | -2n-23=4n+37 | | 3-5x-1/10=x-1/5-x-3/2 | | 1/3-1/8= | | X+8=-5x+20 | | t-5=-7+3t | | 20z-33=40 | | 4(2x+4)+2(3x-5)= | | 9d-1d+2d-9=4d | | 2xy+5x=63 | | Z/10-5=6 | | 23-16.6=x | | x*x=16.6 | | -5+7x=7x+5 | | -5+12=47 | | 8(-2+x)-4x=32 | | 1/12-2/3m=1/3 | | 2a+7=4a-2 | | -4f+5=f+9f+5 | | x*x=14.6 | | 4(a+5)-2(a-5)= | | 12(x+3)=4(2x+9)+7x | | 5x/3-4=2x/5 | | 6g+2(4g-3)+10=32 | | 5=y+9 | | -30=-5/3(x=25) | | m/-4=5=14 | | -7r+6=-15 | | 5x-18=6x+8 |